Empowering Women Through Self-Help Groups and Microcredit Interventions: An Analysis - Elizabeth Joey Henriques (Australasian Accounting Business and Finance Journal, 2024)
Microcredit has emerged as a powerful tool to foster economic development by promoting entrepreneurship and facilitating women empowerment. The concept of empowerment is multifaceted, encompassing many aspects. The present study is an attempt to study the impact of microcredit and Self-Help Groups (SHGs) on the social, economic, and political profile of the women members. The study is based on both primary and secondary data sources. A questionnaire was administered to 780 respondents drawn from 185 SHGs in the State of Goa in India. For the purpose of the study, women's empowerment has been defined as a summation of three constructs: economic empowerment, social empowerment, and political empowerment. Changes in the perception of women to the different attributes of empowerment have been analysed adopting a pre and post SHG membership approach and the paired t test has been used for hypothesis testing. An Empowerment Index has been used to identify the level of empowerment. The Chi- Square test has been used to determine the interdependence of the level of empowerment and various socio-economic variables. The findings indicate that SHGs and microcredit interventions have positively impacted women. In terms of social empowerment, the maximum impact has been on the mobility and confidence levels of the members. The decision to vote, however, is predominantly determined by the spouse and other family members.
Keywords: Women; Empowerment; Self-Help Groups; Micro credit; Confre; Goa